Ten year follow up of patients with single vessel coronary artery disease that was suitable for percutaneous transluminal coronary angioplasty. Issue 3 (March 1988) - Danchin, N; Brengard, A; Ethevenot, G; Briançon, S; Cuillière, M; Aliot, E; Pernot, C; Gilgenkrantz, J M; Mathieu, P; Cherrier, F
Abstract : The 10 year outcome of patients with single vessel coronary artery disease who underwent coronary angiography more than 10 years before and who would have been potential candidates for percutaneous transluminal coronary angioplasty had it been available then is reported. Long term follow up data were obtained in 96 (91 men, five women; mean age 48 years) of 105 consecutive patients with single vessel coronary artery disease (greater than 70% stenosis), judged suitable for coronary angioplasty. Fifty patients had coronary bypass surgery within six months of catheterisation (surgical group) and 46 were treated medically (medical group). At entry to the study more patients in the surgical group had unstable angina, but fewer had a previous history of myocardial infarction. Ten year survival was 91% and remained excellent in all the subsets analysed. Moreover, the quality of life of these patients was good. Over the 10 year follow up, 16 (36%) of the patients treated medically and 13 (26%) in the surgical group were admitted to hospital because of cardiovascular events (including late coronary surgery in four of the patients treated medically). Lastly, 54/69 (78%) of the patients who were employed before catheterisation resumed work and 29 (42%) were still employed 10 years later. Although these data must be interpreted with care because of the limitations inherent in all retrospective studies, it appears that the long term results of conventional medical or surgical treatment are excellent in patients with single vessel coronary artery disease in whom percutaneous transluminal coronary angioplasty is now an option.